Tindakan Membuka Identitas Pasien Terkonfirmasi Covid-19 oleh Rumah Sakit Berdasarkan Hak Asasi Manusia dan Hukum Pidana - Hwian Christianto; Ervin Dyah Ayu Masita Dewi (Jurnal HAM, 2022)
Hospitals face dilemma concerning covid 19 patient identity. On one side, they are imposed by an obligation to secure the confidentiality of patients with covid 19, but on the other side, they must inform the patient's identity to government. The act of revealing identity of patient with covid 19 taken by the hospital raises debate from human rights perspective and whether it violates the law or not. The normative Juridical method was used to solve this problem through approaches of prevailing law and concepts on human rights in medical ethics and unlawful act. The result showed that revealing a patient's identity with covid 19 based on nonmaleficence principle in bonum commune context can be lawful and fulfill human rights on behalf of covid 19 management. Moreover, based on the penal code, revealing the identity of a patient with covid 19 taken by a hospital is lawful in an emergency setting (noodtoestand).